Vaccination strategies for the prevention of meningococcal disease - Scott Vuocolo; Paul Balmer; William C. Gruber; Kathrin U. Jansen; Annaliesa S. Anderson; John L. Perez; Laura J. York (Taylor & Francis Group, 2018)
Routine prophylactic vaccination and mass vaccination strategies have been used to control both endemic and epidemic disease caused by Neisseria meningitidis globally. This review discusses real-world examples of these vaccination strategies, their implementation, and outcomes of these efforts, with the overall goal of providing insights on how to achieve optimal control of meningococcal disease through vaccination in varied settings. Tailoring immunization programs to fit the needs of the target population has the potential to optimally reduce disease incidence.